2016
DOI: 10.1183/13993003.01588-2015
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up of pulmonary right-to-left shunt in hereditary haemorrhagic telangiectasia

Abstract: Pulmonary arteriovenous malformations (PAVMs) are associated with severe neurological complications in hereditary haemorrhagic telangiectasia (HHT). Transthoracic contrast echocardiography (TTCE) is recommended for screening of pulmonary right-to-left shunts (RLS). Although growth of PAVMs is shown in two small studies, no studies on follow-up with TTCE exist.All HHT patients underwent a second TTCE 5 years after initial screening. Patients with a history of PAVM embolisation were excluded. Pulmonary RLS grade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 18 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…The current core networks are interstitial lung diseases [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], cystic fibrosis [22][23][24][25], pulmonary hypertension [26][27][28][29][30][31], primary ciliary dyskinesia [32][33][34][35][36][37], non-cystic fibrosis bronchiectasis [38][39][40], α 1 -antitrypsin deficiency [41], mesothelioma [42], chronic lung allograft dysfunction [43][44][45] and "other rare lung diseases" (e.g. pulmonary malformations, congenital central hypoventilation syndrome etc) [46][47][48][49]. In addition to these thematic subgroups, ERN-LUNG is also organised into functional committees whose aims are to tackle overarching topics affecting all of the current and future core networks, including research and clinical trials, ethical issues, registries and biobanks, patient-reported outcomes and ...…”
mentioning
confidence: 99%
“…The current core networks are interstitial lung diseases [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21], cystic fibrosis [22][23][24][25], pulmonary hypertension [26][27][28][29][30][31], primary ciliary dyskinesia [32][33][34][35][36][37], non-cystic fibrosis bronchiectasis [38][39][40], α 1 -antitrypsin deficiency [41], mesothelioma [42], chronic lung allograft dysfunction [43][44][45] and "other rare lung diseases" (e.g. pulmonary malformations, congenital central hypoventilation syndrome etc) [46][47][48][49]. In addition to these thematic subgroups, ERN-LUNG is also organised into functional committees whose aims are to tackle overarching topics affecting all of the current and future core networks, including research and clinical trials, ethical issues, registries and biobanks, patient-reported outcomes and ...…”
mentioning
confidence: 99%
“…For example, in a follow-up study of 20 patients over 11–13 years, nine patients showed slow radiographic progression (estimated at 0.3–2 mm/year) while 11 remained unchanged 11–13. If an increased right-to-left shunt can be taken as indicative of growth of PAVM, it was observed in 18% of 200 patients with HHT followed over 5 years 14. It appears that PAVMs as part of HHT are more prone to enlargement than ‘sporadic’ PAVMs that often remain stable 3 11.…”
Section: Discussionmentioning
confidence: 99%
“…Strokes, brain abscesses, respiratory failure, life- threatening bleeding and haemothorax are considered the most severe complications reflected in the morbidity and mortality of PAVMs. PAVMs are normally stable with respect to growth; however, 25% will enlarge slowly, usually at a rate of 0.3–2 mm/year 22. PAVMs are not known to spontaneously resolve.…”
Section: Discussionmentioning
confidence: 99%